2019
DOI: 10.1186/s13048-019-0583-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the umbilical cord Blood’s anti-Mullerian hormone level in the newborns of mothers with polycystic ovary syndrome (PCOS) and healthy mothers

Abstract: BackgroundPolycystic ovary syndrome (PCOS) is one of the most common endocrine diseases. At present, the cause of the disease is not fully understood, but many studies have shown that PCOS is associated with genetic and environmental factors. The present study aimed to assess the umbilical cord blood’s Anti-mullerian hormone (AMH) level in the newborns of mothers suffering from PCOS comparing to healthy mothers.MethodsThis prospective cohort study was conducted on 120 pregnant women with PCOS, who were selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 45 publications
(43 reference statements)
1
10
0
Order By: Relevance
“…First, the history of hospital controls was not elaborated in one study [ 13 ]. Secondly, there was no reliable medical of patients provided in one prospective cohort study [ 26 ], in which the control group was recruited from another resource of population that is different from the case group. In addition, another observational study [ 24 ] recruited hospital controls instead of community controls while a reliable exposure record was absent.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…First, the history of hospital controls was not elaborated in one study [ 13 ]. Secondly, there was no reliable medical of patients provided in one prospective cohort study [ 26 ], in which the control group was recruited from another resource of population that is different from the case group. In addition, another observational study [ 24 ] recruited hospital controls instead of community controls while a reliable exposure record was absent.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies were excluded for reasons after screening the full texts: 1 study was a review, 2 studies reported no AMH outcomes, and 2 studies were lack of extractable data. Finally, 6 papers including 3 case-control studies, 2 prospective cohort studies, and 1 cross-sectional study were included in this review [13,[22][23][24][25][26]. The selection process was documented with a flowchart of Preferred Reporting Items for Systematic Reviews and Meta-Analyses (Fig.…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations